2019
DOI: 10.2478/s11686-019-00124-x
|View full text |Cite
|
Sign up to set email alerts
|

Review of Cystic Echinococcosis in Nigeria: A Story of Neglect

Abstract: Purpose Cystic echinococcosis (CE) caused by Echinococcus granulosus sensu lato is a widespread zoonotic disease of global concern. In Nigeria, the exact picture/status of CE is unclear, as most of the states are largely uninvestigated. Yet, as with every parasitic zoonosis, the first step towards planning a comprehensive management and control programme involves assessment of available national/regional prevalence data, host range, and risk factors at play in the transmission dynamics. Methods Published artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 70 publications
(87 reference statements)
0
6
1
Order By: Relevance
“…These results are contrary to those obtained from a study conducted on ruminants in north east Morocco by El Brebri et al [12]. According to them, females are more vulnerable to echinococcosis infection than males [13]. This difference could also be explained by the lower number of female animals examined in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…These results are contrary to those obtained from a study conducted on ruminants in north east Morocco by El Brebri et al [12]. According to them, females are more vulnerable to echinococcosis infection than males [13]. This difference could also be explained by the lower number of female animals examined in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…However, a study from Nigeria recently reported a CE infection in a dromedary that was caused by the G1 genotype (Ohiolei, Yan, Li, Isaac, et al, 2019). Thus, the rareness of the G1 genotype in the sub‐region could be due to poor surveillance as most countries in the sub‐region are largely uninvestigated (Deplazes et al., 2017; Ohiolei, Yan, Li, Isaac, et al, 2019; Ohiolei, Yan, Li, Zhu, et al, 2019). This scarcity of data and the uneven distribution of the available studies in the sub‐region could make the observation relatively less representative.…”
Section: Discussionmentioning
confidence: 99%
“…In Nigeria, although the high prevalence of CE in livestock attracted a lot of concern between 1970 and 1990, not much has been done lately (see the review by Ohiolei et al ., 2019b). In humans, the seemingly low CE prevalence has been attributed to poor surveillance, lack of differential diagnosis and poor knowledge by medical personnel (Fasina & Ogun, 2017; Ohiolei et al ., 2019b).…”
Section: Resultsmentioning
confidence: 99%
“…In Nigeria, although the high prevalence of CE in livestock attracted a lot of concern between 1970 and 1990, not much has been done lately (see the review by Ohiolei et al ., 2019b). In humans, the seemingly low CE prevalence has been attributed to poor surveillance, lack of differential diagnosis and poor knowledge by medical personnel (Fasina & Ogun, 2017; Ohiolei et al ., 2019b). In our previous study, where we reported the G6/7 genotype as being responsible for CE infection in livestock, the absence of the G1 genotype could have been a result of sample size limitation, as emphasized (Ohiolei et al ., 2019a).…”
Section: Resultsmentioning
confidence: 99%